(untitled) (Pursuits: A Journal of English Studies, 2025)
This study reflects the value that citizens place on their own nation. It depicts the way citizens live, where government bureaucrats and industrial employers enforce their authority. Their actions often place them in opposition to a citizen. W. H. Auden, in his poem “The Unknown Citizen,” critiques the degrading effects of bureaucratic domination and misunderstanding. The individual’s rights as a citizen is reduced to an anonymous figure defined more by the Bureau of Statistics than by personal identity. Through subtle satire and irony, Auden exposes how societal norms prioritize efficiency and tradition over citizen’s individuality, autonomy, and freedom. This study employs a qualitative approach to explore how government bureaucracy and industrial owners shape and control a citizen’s personal identity, freedom, and emotions. It adopts an interpretative method to evaluate the value of a citizen’s life. It examines the cost and sacrifice required to maintain the idealized perfect citizen in an objective, system-driven world. This is Auden’s clear awareness arising from his knowledge of Marxist liberty theory; its analysis investigates how bureaucratic and capitalist structures diminish citizen’s capacity for independent thought and action, making him victim of their agency. This research takes account of the citizen’s career covering present, past, and future. Auden’s poem serves as both a critique of modern society’s dehumanizing mechanisms and a reflection on the commodification of human life. Briefly, the research throws light on citizen’s crisis of personal autonomy versus the tyranny of the national mafias.